Identification and Characterization of a Novel Chromosomal Aminoglycoside 2′-N-Acetyltransferase, AAC(2′)-If, From an Isolate of a Novel Providencia Species, Providencia wenzhouensis R33 - Zhou, Kexin; Liang, Jialei; Dong, Xu; Zhang, Peiyao; Feng, Chunlin; Shi, Weina; Gao, Mengdi; Li, Qiaoling; Zhang, Xueya; Lu, Junwan; Lin, Xi; Li, Kewei; et al. (Frontiers in Microbiology, 2021)
Multidrug-resistant bacteria from different sources have been steadily emerging, and an increasing number of resistance mechanisms are being uncovered. In this work, we characterized a novel resistance gene named aac(2′)-If from an isolate of a novel Providencia species, Providencia wenzhouensis R33 (CCTCC AB 2021339). Susceptibility testing and enzyme kinetic parameter analysis were conducted to determine the function of the aminoglycoside 2′-N-acetyltransferase. Whole-genome sequencing and comparative genomic analysis were performed to elucidate the molecular characteristics of the genome and the genetic context of the resistance gene-related sequences. Among the functionally characterized resistance genes, AAC(2′)-If shares the highest amino acid sequence identity of 70.79% with AAC(2′)-Ia. AAC(2′)-If confers resistance to several aminoglycoside antibiotics, showing the highest resistance activity against ribostamycin and neomycin. The recombinant strain harboring aac(2′)-If (pUCP20-aac(2′)-If/DH5α) showed 256- and 128-fold increases in the minimum inhibitory concentration (MIC) levels to ribostamycin and neomycin, respectively, compared with those of the control strains (DH5α and pUCP20/DH5α). The results of the kinetic analysis of AAC(2′)-If were consistent with the MIC results of the cloned aac(2′)-If with the highest catalytic efficiency for ribostamycin (kcat/Km ratio = (3.72 ± 0.52) × 104 M−1·s−1). Whole-genome sequencing demonstrated that the aac(2′)-If gene was located on the chromosome with a relatively unique genetic environment. Identification of a novel aminoglycoside resistance gene in a strain of a novel Providencia species will help us find ways to elucidate the complexity of resistance mechanisms in the microbial population.